Analisis Strategi Dalam Meningkatkan Pembangunan Pada Sektor Pertanian Di Desa Tondegesan Induk Kecamatan Kawangkoan Kabupaten Minahasa - Langi, Debora Claudia; Rumapea, Patar; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : The agricultural sector is the dominant sector of national and regional development regarding the role of agriculture in employment, income generation and social welfare, economic growth and the creation Domestic gross regional product (GDP ) and foreign exchange through exports. Therefore, the research is the analysis of Strategy to Improve Agricultural Sector Development In Tondegesan In the village of the District Parent Kawangkoan Minahasa .This research used Qualitative Research Methods using data analysis techniques SWOT. Analysis of internal factors produce factors strengths and weaknesses. Strengths factors is fertile Potential Land Resources, Commodity excels as a primary requirement, Human Resources 75,06% is Farmer, Having a farmer institution, farmer group businesses management, and Strategy of market place. Weakness factors is Lack of support for government benefits, Farmers have limited access to capital, lack of control from PPL, Lack of Knowledge and Skills Farmer, limited facilities and infrastructure, Weak Agricultural Technology. External factors generating opportunities and threats factors. Opportunities factors is market needs, The development of the fertilizer industry, agroindustrial production machine tool industry, and Technological Development. Treatments Factors is capital through bank loans, Price of Fluctuations, Fluktuasi, and trade globalization.Based on the SWOT analysis, set out six strategies, is Increased production and productivity in the agricultural sector, increases the potential of human resources, and market information functions, Empowerment agricultural institutions, Increasing the added value and competitiveness of primary agricultural products, procurement of basic needs in agriculture, Creating policies in favour on farmers.Key Words :Analysis Of Strategies To Enhance Agricultural Development, SWOT.